Reengineering Business Process Manufacturing Company Sales Module Using Odoo V12.0 Application - Rika Hari Wahyuni; I Made Sukarsa; Dewa Made Sri Arsa (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2021)
The manufacturing industry applies the use of ERP to run corporate business processes, build good communication and improve service quality. This study aims to provide a Business Process Reengineering proposal to the sales department using the Odoo V12.0 so that the system can be integrated. The methodology used in this research is Business Process Reengineering, where the research only focuses on the sales field. Existing business processes, namely purchasing products, sales orders and invoicing manuall. Reengineering that has been carried out is the product sales process, the sales order process, and the payment process. Reengineering has been carried out quite well by using the User Acceptance Test method and obtaining agreed responses as the greatest value in every aspect. The results obtained are based on 5 categories, namely content items by 63%, module items by 53%, multimedia element items by 88%, navigation aspects by 70% and usability items by 82%. Keywords: Business Process Reengineering, Enterprise Resource Planning, Odoo V12.0, Sales, User Acceptance Test